Controle da poluição do ar por filtração híbrida de material particulado proveniente da indústria siderúrgica - Araújo, Deisy Teles de (Universidade Federal de São Carlos, 2024)
The transmission of specific material by industry poses a serious threat to the environment and human health. The World Health Organization (WHO) World Health Statistics report of 2018 revealed that air pollution was involved in approximately 7 million premature deaths worldwide by 2016, and data from 2022, also from the WHO, showed that more than 99% of the world's population breathes the air that is considered unhealthy. A promising alternative to control air pollution is the hybrid filter. These filters combine traditional gas and solid particle separation equipment, such as electrostatic precipitators and bag filters, in a single device. This project aims to analyze the performance of hybrid filtration in relation to collection efficiency, cake porosity, filtration time and pressure drop in a bench-scale equipment, at different electric field intensities applied to the precipitator. The superficial filtration velocity in the system was 0.047 m.s-1 (2.8 m.min-1) and in the electrostatic precipitator it was 0.74 m.s-1. The electric fields applied to the electrostatic precipitator were 0.0, -2.0 and -4.0 kV.cm-1. The particulate materials tested were phosphate rock and sintering dust, the latter coming from the hoppers of an industrial bag filter. The filter materials tested were polypropylene (PP) and polyester (PE). As a result, as the voltage applied to the precipitator increased, an increase in the collection efficiency was observed in the precipitator and in the filter, causing the efficiency in the hybrid filter to reach values of 100% for some operational conditions investigated. The filter material that presented the best collection efficiency for the tests performed with phosphate rock was polypropylene, while for the sintering powder, both filter materials presented good performance. The porosity values for the sintering powder were similar to both the polypropylene and polyester filtration tests. However, when considering phosphate rock, it is recommended that the tests with polyester resulted in higher porosities than those with polypropylene. The longest filtration time to reach the pressure drop of 100 mmH2O in the hybrid filter tests occurred under the conditions of greatest eclectic field applied to the precipitator. For industrial filters, this result can be translated into a lower frequency of cleaning pulses in the bags, and, consequently, a longer useful life, reducing the costs with the total bag replacement.
Control of air pollution by hybrid filtration of particulate matter from the steel industry
Keywords: Hybrid filtration; Particle matter; Air pollution control; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA